From niche to organoid: Engineering bone tissues through microenvironmental insights - Yan Xu; Lingchao Sheng; Minmin Zhu; Zhengcheng He; Xudong Yao; Hongwei Wu (Journal of Tissue Engineering)
The construction of bone organoids represents a transformative approach in tissue engineering, offering unprecedented opportunities for studying bone biology, disease modeling, and regenerative medicine. The intricate understanding of the skeletal microenvironment, or niche, which governs cellular behavior, tissue organization, and functional maturation, is critical important to construct bone organoid. This review explored insights into the skeletal microenvironment, including the roles of extracellular matrix components, mechanical cues, biochemical signaling, and cellular interactions. It also proposes a foundational strategy how advancements in biomaterials, extracellular matrix, and micro-structure have enabled the precise recapitulation of niche conditions, facilitating the development of physiologically relevant bone organoids. Furthermore, we highlight the applications of these organoids in drug screening, personalized medicine, and bone regeneration. By bridging the gap between niche biology and organoid engineering, this review underscores the potential of microenvironment-driven approaches to revolutionize bone tissue engineering and its translational impact.